Rukūb Jīrūdū wa Lubs Tūbing fī ʿĀdāt al-Zifāf bi Jāmbī fī Ḍawʾ Aḥādīth al-Taṣwīr - Febriansyah, Febriansyah; Fatihunnada, Fatihunnada; Salim, Hasan Basri; Anwar, Saepul; Labbaika, Lingga (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
The interaction and exchange between local culture and Islamic culture dominate in influencing the social system. This research aims to explore the perspective of Hadith on the Gerudo and Topeng celebrations in Jambi. This research relies on an analytical descriptive method based on collecting library data from various paper and electronic sources and field data through observation and interviews. The researcher then used thematic methods in the takhrīj of hadith, involving the search for hadiths based on sentences related to the topic. In analyzing hadith texts, the researcher has employed a contextual method with comparison approach and has compared them with the opinions of ‘ulamā’ who are both supportive and critical of these approaches. The key finding of this research is that the taṣwīr prohibited by the Prophet Muhammad refers to taṣwīr that contains an 'illah or reason for its prohibition. This prohibition applies to taṣwīr used as a rival to Allah's creation, for worship, or due to elements in its form that contradict Islam. Therefore, Gerudo and Topeng are not considered prohibited taṣwīr because current practices no longer embody the reasons for their prohibition.